2016
DOI: 10.4314/ajtcam.v13i1.11
|View full text |Cite
|
Sign up to set email alerts
|

<i>Pterocarpus angolensis</i> crude extracts induce the expression of collagen Type II in articular cartilage <i>in vitro</i>

Abstract: Background: Pterocarpus angolensis (P. angolensis) is a large deciduous tree native to Sub-Saharan Africa. This tree has traditionally been used to treat malaria, gonorrhoea, inflammation and wounds. The use of P. angolensis for tissue engineering has not been explored. This study investigated the potential of the bark and root water extracts of P. angolensis to induce the expression of collagen type II protein in the articular chondrocytes. Materials and Methods: Surface and middle zone chondrocytes, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, the plant extracts at a 50 μg/ml induced apoptosis in the middle zone chondrocytes. In conclusion the findings of this study are of great importance in understanding the mechanisms through which P. angolensis enables the healing of breached tissue [21]. In our laboratory, an (unpublished) in vitro study has observed the enhancement of proliferation and osteogenic differentiation (by increasing alkaline phosphate activity) of C2C12 myoblast cells treated with Pleurostylia capensis crude extract.…”
Section: Role Of Medicinal Plants In Chondrocytesmentioning
confidence: 59%
“…However, the plant extracts at a 50 μg/ml induced apoptosis in the middle zone chondrocytes. In conclusion the findings of this study are of great importance in understanding the mechanisms through which P. angolensis enables the healing of breached tissue [21]. In our laboratory, an (unpublished) in vitro study has observed the enhancement of proliferation and osteogenic differentiation (by increasing alkaline phosphate activity) of C2C12 myoblast cells treated with Pleurostylia capensis crude extract.…”
Section: Role Of Medicinal Plants In Chondrocytesmentioning
confidence: 59%
“…The (DCM/Methanol v / v , 50%) extract of P. angolensis inhibited Plasmodium falciparum chaperones (PfHsp70-z and PfHsp70-1), with IC 50 values of 13.87 and 0.20 µg/mL, respectively [ 14 ]. The crude aqueous extracts of bark and root from P. angolensis enabled the healing of breached tissue and induced an increase in chondrogenesis [ 15 ]. According to our knowledge, no anticancer activities have been reported on the extracts and isolated compounds of P. angolensis .…”
Section: Introductionmentioning
confidence: 99%
“…These plant extracts are also being incorporated in the fabrication of biomaterial scaffolds used in tissue engineering and regenerative medicine. [16][17][18][19] These scaffolds will not only act as medium to transport cells/materials inside or outside the human body, but also take part in the regeneration and activation of cells owing to their plant morphogenetic factor content.…”
mentioning
confidence: 99%
“…In fact, plant extracts are currently seen as potential solutions in the treatment of chronic wounds and speeding up acute healing, reducing longer hospital stay of patients with bone fracture problems due to accidents and medical conditions. They could furthermore act as anti-inflammatory agents in inflammatory diseases as well as alleviate or accelerate OA healing and other joint diseases by increasing collagen type II production in tissue engineering and re-generative medicine, [16][17][18] besides being useful in the pharmaceutical sector for drug production for the treatment of numerous illnesses.…”
mentioning
confidence: 99%